2003
DOI: 10.1034/j.1398-9995.2003.00174.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin (IL)‐4 and to a lesser extent either IL‐13 or interferon‐gamma regulate the production of eotaxin‐2/CCL24 in nasal polyps

Abstract: All together these findings suggest that Th1 and Th2 cytokines may regulate eotaxin-2/CCL24 production in nasal polyps and nonallergic rhinits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…20 Kinetic studies with nasal polyps that were obtained from atopic and nonatopic patients showed that when stimulated ex vivo with IL-4, eotaxin-2 is released within 24 hours from stimulation, which sustained for 96 hours. 30 The results from this study suggest that there might be a longlasting production of eotaxin-2 when IL-4 is released in vivo. In addition, it was shown recently that production of eotaxin-2 and eotaxin-3 by bronchial epithelial cells in vitro was induced by IL-4 or IL-13 alone, which might suggest that these 2 eotaxins could be secreted at sites of T H 2-dominant allergic inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…20 Kinetic studies with nasal polyps that were obtained from atopic and nonatopic patients showed that when stimulated ex vivo with IL-4, eotaxin-2 is released within 24 hours from stimulation, which sustained for 96 hours. 30 The results from this study suggest that there might be a longlasting production of eotaxin-2 when IL-4 is released in vivo. In addition, it was shown recently that production of eotaxin-2 and eotaxin-3 by bronchial epithelial cells in vitro was induced by IL-4 or IL-13 alone, which might suggest that these 2 eotaxins could be secreted at sites of T H 2-dominant allergic inflammation.…”
Section: Discussionmentioning
confidence: 89%
“…As for CCR3 ligands, such as eotaxins (CCL11, CCL24 and CCL26) and CCL13/MCP-4, CCL5/RANTES and CCL28/ MEC are produced at the allergic inflammatory sites. 8,9) We propose that the eosinophils recruited at the inflammatory sites could contribute to enhance allergic inflammation not only as cells producing MBP or ECP, but also as cells producing eotaxins.…”
Section: Discussionmentioning
confidence: 99%
“…6,7) Recent investigations on atopic and nonatopic individuals indicate that eotaxin-2/CCL24 is produced in skin and lung following exposure to antigen. 8) Further, IL-4 was found to be the major stimulus for eotaxin-2/CC24 production from nasal polyps, and in addition, IL-13 and IFN-g were also involved, 9) while differential production of eotaxin subfamilies has not been elucidated.…”
mentioning
confidence: 99%
“…Eleven consecutive patients exhibiting JMADUE (two women and nine men, mean age 18 (range [13][14][15][16][17][18][19][20][21][22] years at the time of examination in the neurology clinic at Kyushu University Hospital) were enrolled in this study. Patients one through five were the same as those in a previous report [4].…”
Section: Subjectsmentioning
confidence: 99%